Implementasi pembelajaran fully online e-learning berbasis moodle - Fitria Fauziah Hasanah; Yuli Fauziah Setiawati; Oyib Fauziah Sulaeman (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The development of human civilization has an impact on the presence of technology which is the most inherent part of life, including in the education sector. 2020 is the year that makes most areas of life undergo changes due to the Covid-19 pandemic. In the field of education, the Covid-19 pandemic makes learning must be carried out online and no learning as usual is carried out face-to-face at school. Each educational institution has its own way of implementing learning during the pandemic, various applications and online learning strategies have become a new culture for educators and students. This study aims to analyze the implementation of fully online e-learning based on moodle used in SDIT Lukman Al Hakim Sleman Yogyakarta and to determine the supporting factors and inhibiting factors. This research is a qualitative research. The results showed the implementation of fully online e-learning based on moodle at SD IT Lukman Al Hakim Sleman Yogyakarta that learning was carried out online from the opening stage at the beginning of learning, then the learning process stage and the closing stage, but at three stages using a platform different. The supporting factor for fully online e-learning based on moodle is because schools provide paid service facilities so that the implementation of learning does not experience different capacity limitations with unpaid services, while the inhibiting factor is that there are still students who experience difficulties in online learning due to unstable networks. in the student's area.